IMPLEMENTASI STRATEGI KAYANG TERHADAP KEBERHASILAN PAUD INKLUSI KASYA DAY CARE CENTER AND SCHOOL BANDA ACEH (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Basically, all children have the same rights to get education, including children with special needs. Teachers must be able to understand and think about what learning strategies are suitable for children with special needs, because children with special needs require special treatment in educating or teaching them. Inclusive PAUD is an educational institution intended for children with special needs, in addition to children with special needs, many students have also registered in Kasya Inclusion PAUD. This study aims to analyze the implementation of learning strategies in the Kasya Day Care Center and School Banda Aceh Inclusion PAUD, namely the â€œkayangâ€ strategy, through the library research method. From the results of this study, it can be concluded that the â€œkayangâ€ strategy has had a huge impact on the progress and success of the Kasya Day Care Center and School Banda Aceh Inclusion PAUD.